Outcomes of Presurgical Nasoalveolar Molding using Modified Nostril Retainers in Patients with Unilateral Cleft Lip and Palate at an Average Follow-up of 2 Years - Serap Titiz Yurdakal; Ekrem Oral; İbrahim Erhan Gelgör (Galenos Yayinevi, 2023)
Objective: Presurgical nasoalveolar molding (PNAM) using a modified nostril retainer is a new treatment approach. This study aimed to evaluate the outcomes of early nasal molding using this approach with an average follow-up of 2 years in patients with severe unilateral cleft lip and palate. Methods: This retrospective study included 18 patients with unilateral cleft lip and palate without genetic syndromes who underwent PNAM with modified nostril retainers. The Grayson technique was employed with an intraoral plate to approximate cleft segments. Nasal molding was initiated before reducing the cleft width to 5 mm. Measurements, including alar base height ratio (ABHR), nasal floor width ratio (NFWR), columellar length ratio (CLR), columellar angle (CA), and nostril axis inclination on the cleft and non-cleft sides (NAI-C and NAI-NC, respectively), were calculated from standard photographs taken before PNAM (T1), after PNAM (T2), after an average of 1.81 months post-surgery (T3), and after an average of 2.2 years after T3 (T4). Pairwise comparisons of values at the four time points were conducted. Results: NFWR, CLR, CA, NAI-C and NAI-NC significantly increased after PNAM (p<0.05). However, no significant change was observed in ABHR (p>0.05) from T1 to T2. These outcomes were maintained at T4, and no patient developed a mega nostril. Conclusion: The use of a modified nostril retainer for nasal molding appears to provide stability during the high probability of relapse reported in the literature.